A Novel Lipid Prognostic Signature of ADCY2, LIPE, and OLR1 in Head and Neck Squamous Cell Carcinoma - Gao, Xiaolei; Zhao, Na; Dong, Liying; Zheng, Xuan; Zhang, Yixin; Ding, Chong; Zhao, Shuyan; Ma, Zeyun; Wang, Yixiang (Frontiers in Oncology, 2021)
Background: Head and neck squamous cell carcinoma (HNSCC) is characterized by a high frequency of lymph node metastasis and a high mortality. Lipid metabolic reprogramming is an emerging carcinogen as its role in fulfilling cancer growth and spread. However, little is known about the correlation between lipid metabolism and HNSCC. Material and Methods: Expressions of lipid-related genes were obtained from the Cancer Genome Atlas (TCGA) and Gene expression Omnibus (GEO) databases for differential and functional analyses. A total number of 498 patients from TCGA with complete information were included to identify a lipid-related prognostic signature (LRPS), based on ADCY2, LIPE and OLR1, by using univariate and multivariate Cox regression analyses. LRPS-high and LRPS-low groups were accordingly divided to pathway and cell enrichment analyses. Results: LRS-low patients had a better overall survival and free to relapse than LRS-high ones in HNSCC. LRPS-high group was significantly related to perineural invasion of cancer, cancer-related pathways, high TP53 mutation rate, high proportion of natural killer T cells (NKT), dendritic cells, monocytes, Treg, M1 and M2 macrophages infiltration in HNSCC tumor tissues. Conversely, LRPS-low group correlated with DNA damage-related and T cells-regulated pathways, low frequency of mutated TP53, high infiltration of B cells, CD4+ effector cells including Th1 and Th2. Conclusion: LRPS has a potential to be a promising indicator of overall survival, prognosis, TP53 status and immune characteristics in HNSCC.